Offshoring and labor market outcomes - Ekwunwa, Obiageli (Kansas State University, 2022)
This report focuses mainly on the impact of offshoring activities on labor market. An in-depth review of economists' empirical work indicates that the effect of increasing offshoring depends on the locations, tasks, and industries of the offshoring activity. In particular, increasing offshoring activities to low-income countries negatively affects most-routine workers' wages and positively affects intermediate-routine workers' wages. However, increasing offshoring to high-income countries hurts intermediate-routine workers' wages and benefits most-routine workers' wages on average. Moreover, we find a net positive effect of increasing offshoring activities on domestic employment despite substantial job loss; however, the magnitude depends on the industry revenue level of the offshoring firm.
Keywords: Offshoring; Foreign direct investment; Wages; Employment